Approaches to modeling cancer metastasis: from bench to bedside - Sun, Leiyu; Zhou, Yajuan; Yin, Maoxu; Wang, Fei; Yang, Lijuan (Frontiers in Oncology, 2025)
Cancer metastasis modeling requires multidisciplinary approaches that integrate experimental, computational, and clinical research to unravel the complexities of cancer spread). By deepening our understanding of the metastatic process, researchers can efficiently and precisely develop targeted therapies and personalized treatment strategies to relieve the burden of metastasis on patients. In this review, we highlight the critical roles of experimental models in advancing knowledge of metastasis, identifying therapeutic targets, evaluating treatment strategies, and improving patient outcomes. These models serve as essential tools for translational research and drug discovery in the fight against metastatic cancer